The effect of an intronic polymorphism on alcohol dehydrogenase expression in Drosophila melanogaster. - Laurie, C.C.; Stam, L.F. (Genetics, 1994)
Several lines of evidence indicate that natural selection controls the frequencies of an allozyme polymorphism at the alcohol dehydrogenase (Adh) locus in Drosophila melanogaster. However, because of associations among sequence polymorphisms in the Adh region, it is not clear whether selection acts directly (or solely) on the allozymic site. This problem has been approached by using in vitro mutagenesis to distinguish among the effects on Adh expression of individual polymorphisms. This study shows that a polymorphism within the first Adh intron (delta 1) has a significant effect on the level of ADH protein. Like the allozyme, delta 1 shows a geographic cline in frequency, indicating that it may also be a target of natural selection. These results suggest that multisite selection models may be required to understand the evolutionary dynamics of individual loci.